Legislating Against Hate Crime in New Zealand: The Need to Recognise Gender-Based Violence - Brown, Charlotte (Victoria University of Wellington Law Review, 2004)
Section 9(1)(h) of the Sentencing Act 2002 provides that hate crime is to be taken into account as an aggravating factor when sentencing. Yet gender is excluded from the listed grounds of hostility. This article critically examines the exclusion of gender-based hate crime in New Zealand in relation to criminal sentencing. It advocates that there is a need to recognise such hate crime and proposes a reformulated section 9(1)(h) to achieve this.